Dokładność statystycznej metody reprezentacyjnej a zmiany wielkości zasobów drzewnych w kolejnych rewizjach urządzania lasu - Jabłoński, Marek (Leśne Prace Badawcze, 2013)
Since 1967, when the Polish State Forests were first inventoried, a continuous increase in the volume of growing stock has been recorded. This increase in timber resources is mainly the result of sustainable forest management. However, during this time period inventory methods have been changed a few times and this may have affected the estimates of of wood resources. Since 2011 new instructions have been in place for forest management plans in the Polish State Forests. Despite this, the method of taking forest inventories remained consistent with the previous guidelines. This should allow us to consider changes in the volume of growing stock in relation to inventory methods and their accuracy. In this paper, the results of growing stock estimations based on two assessments made using stratified random sampling are compared. After five years of inventories made for forest management plans, 422 sample plots in two forest districts were measured within 15 strata. Predicted age classes structure at the beginning of successive management plans was used to determine new strata. Data from two inventories were compared on the basis of age class. In addition, data from the State Forests Information System i.e. updated stand level inventory data (on felling and tree growth) were analyzed. Comparing data from the two inventories, in three of seven age classes there was a decrease in the volume of growing stock after a five year period. We found no rational explanation for this. The extent of felling in the analyzed stand was very low, as confirmed by data from State Forests database. However, the largest decrease in volume was 1.5%, whereas the accuracy of growing stock assessment of discussed age class was estimated at some 9% in 2006 and 8% in 2011. Hence, from statistical viewpoint there was no differences between the results of both inventories. However, the differences between volume of growing stock of examined age classes, updated in the Information System of the State Forests and results of assessments by stratified sampling are less than 95% confidence intervals for means of samples. Because of that, updated information could be used in the long term management planning. The results clearly suggest that changes of growing stock, estimated as a difference between two assessments, should be interpreted in conjunction with the accuracy of these inventories. The accuracy of sampling should be also taken into account when creating management plans.